ANALISIS IMPLEMENTASI STANDAR PELAYANAN MINIMAL DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT UMUM DAERAH (RSUD) I LAGALIGO WOTU LUWU TIMUR - Desak Nyoman Suartini; Andi Syamsul Bachri Jamal; Anas Budi (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Hospital Minimum Service Standards (SPM) are provisions for hospitals issued by the Minister of Health of the Republic of Indonesia in the context of government efforts to ensure the quality of hospital services. This Minimum Service Standard can be used as a guideline for the quality of service for every hospital in Indonesia. The Minimum Service Standard (SPM) is a quality guideline issued by the Minister of Health regarding the minimum service that must be provided by the hospital, where each hospital is required to assess and provide services by the Minimum Service Standards (SPM). Objectives: The purpose of this study was to determine the relationship between infrastructure and human resources with minimum service standards in the emergency department of the general hospital area I Lagaligo, East Luwu. Methods: The type of research used in this research is descriptive-analytic with a cross-sectional approach. This research was conducted from June to August 2020 in the Emergency Room I Lagaligo East Luwu General Hospital. Sample selection with total sampling technique. The research subjects were 33 respondents. the instrument used is a questionnaire. analysis used the chi-square test. Results: Based on the results of this study, it showed that there is a relationship between infrastructure and minimum service standards with a value of p-value = .008, there is a relationship between human resources and minimum service standards with a value of p-value = .000. Conclusion: There are infrastructure facilities that can be used directly by health workers for the benefit of patients in the form of tools, materials, comfortable rooms, and others. The human resources in the emergency department of Lagaligo Wotu Hospital are of good quality.